FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MINING AND MINING SERVICES DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2014)
This study aims to examine the factorsLiquidity, Growth, firmsize, profitability and asset structure. The population in this study is the Mining and Mining Services companies listed in Indonesia Stock Exchange. Sampling using purposive sampling method. The study period of 2008-2012 analytical tool used is multiple regresion. The results showed that the structure of the variableAsset structure significant positive effect on the capitel structure and liquidity adversely affect the capital structure. While the Liquidity, Growth, Firm Size, Profitability and Asset structure. Keywords: Capital Structure, Liability, Growth, Firm Size, Profitability danAsset Structure